PENGARUH PEMBERDAYAAN GURU USAHA KESEHATAN SEKOLAH DALAM ASUHAN KEPERAWATAN GIGI TERHADAP PENINGKATANI ORAL HYGIENE PADA SEKOLAH DASAR : STUDI DI EMPAT SEKOLAH DASAR WILAYAH KERJA PUSKESMAS I DENPASAR SELATAN - Ni Ketut Nuratni (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
Poor oral circumstances because of untreated caries to children impacted their growth, welfare and affect the quality of their living. Prevention of dental and oral disease through empowerment can be dental and oral health training to commnity leaders, including school health teachers as community leader in school. Purpose of this research to know the efect of teacher empowerment in nursing  care  to increased dental and oral higiene students in elemennry school of the work arca Healh Center I South Denpasar. This research is a quasi experimental with pre-and posttest control group design. Using total of 186 sampling: 94 students intervention group and 92 students control group, drawn from the entire fifth grade student from four elementary schools selected by purposive sampling of 18 public elementary schools in the work area Health Center I South Denpasar. Mann Whitney test result is reduction in plaque index the aveage of 2.65 with p0.001, significant diference between the mean difference in plaque index intervention group with the control group. Showed no effect of the school health teacher empowerment in dental nursing care of the dental plaque index decrease, so will afect the increase in the OraI Higyiene of elemennry schools community in the work area Health Center I South Denpasar. School health teacher are advised to apply the learning materials that obtained from the empowermant to all of students